European Dermatology Forum guidelines on topical photodynamic therapy 2019 Part 2: emerging indications – field cancerization, photorejuvenation and inflammatory/infective dermatoses. (5th December 2019) - Morton, C.A.; Szeimies, R.‐M.; Basset‐Séguin, N.; Calzavara‐Pinton, P.G.; Gilaberte, Y.; Hædersdal, M.; Hofbauer, G.F.L.; Hunger, R.E.; Karrer, S.; Piaserico, S.; Ulrich, C.; Wennberg, A.‐M.; et al.
Abstract: In addition to approved indications in non‐melanoma skin cancer in immunocompetent patients, topical photodynamic therapy (PDT) has also been studied for its place in the treatment of, as well as its potential to prevent, superficial skin cancers in immune‐suppressed patients, although sustained clearance rates are lower than for immune‐competent individuals. PDT using a nanoemulsion of ALA in a daylight or conventional PDT protocol has been approved for use in field cancerization, although evidence of the potential of the treatment to prevent new SCC remained limited. High‐quality evidence supports a strong recommendation for the use of topical PDT in photorejuvenation as well as for acne, refractory warts, cutaneous leishmaniasis and in onychomycosis, although these indications currently lack approvals for use and protocols remain to be optimized, with more comparative evidence with established therapies required to establish its place in practice. Adverse events across all indications for PDT can be minimized through the use of modified and low‐irradiance regimens, with a low risk of contact allergy to photosensitizer prodrugs, and no other significant documented longer‐term risks with no current evidence of cumulative toxicity or photocarcinogenic risk. The literature on the pharmacoeconomics for using PDT is also reviewed, although accurate comparisons are difficult to establish in different healthcare settings, comparing hospital/office‐based therapies of PDT and surgery with topical ointments, requiring inclusion of number of visits, real‐world efficacy as well as considering the value to be placed on cosmetic outcome and patient preference. This guideline, published over two parts, considers all current approved and emerging indications for the use of topical photodynamic therapy in Dermatology prepared by the PDT subgroup of the European Dermatology Forum guidelines committee. It presents consensual expert recommendations reflecting current published evidence.